1947
DOI: 10.1111/j.1151-2916.1947.tb19556.x
|View full text |Cite
|
Sign up to set email alerts
|

Alumina‐silica Relationship in Glass*

Abstract: Assuming from a consideration of silicate minerals that aluminum should replace silicon in silicates, the authors investigated the system Naz0-Ca0-SiO~-Alz03. Densities and refractive indices have been determined and molecular refractions have been calculated. Partial molecular refractivities of & 0 3 indicate a coordination number of 4 for aluminum and deviate appreciably from values for compounds in which aluminum has a coordination number of 6. Interionic distances have been calculated for Si-0 and A1-0.As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1954
1954
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…This agrees with the molar volume behavior of glasses and melts which is related to oxygen coordination. For several series of silicate glasses to which Al 2 O 3 was added, the partial volume increases linearly as a function of Al 2 O 3 content up to 40 cm 3 /mol (Stafford and Silverman, 1947). This volume is totally different to that observed at room temperature for a-Al 2 O 3 (corundum) equal to 25 cm 3 /mol, where Al occurs as [6] Al.…”
Section: Liquid Aluminamentioning
confidence: 99%
“…This agrees with the molar volume behavior of glasses and melts which is related to oxygen coordination. For several series of silicate glasses to which Al 2 O 3 was added, the partial volume increases linearly as a function of Al 2 O 3 content up to 40 cm 3 /mol (Stafford and Silverman, 1947). This volume is totally different to that observed at room temperature for a-Al 2 O 3 (corundum) equal to 25 cm 3 /mol, where Al occurs as [6] Al.…”
Section: Liquid Aluminamentioning
confidence: 99%
“…In 1947, Safford et al investigated the interaction between Al 3+ and Si 4+ in glasses. Their study indicated that Al 3+ can play the role of the network former by virtue of isomorphic replacement with Si 4+ ion in the random tetrahedral configuration and the interstices of the open structure accommodate cations such as Na + and Ca 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…3 In addition to different glass formers, numerous oxides of alkaline earth, heavy metal, and rare-earths along with their fluoride counterparts have been tried to formulate suitable host matrix to develop nano-crystalline alkaline-earth fluorides (CaF 2 , BaF 2 , SrF 2 ), heavy-metal fluorides (CdF 2 , PbF 2 ), alkaline earth/alkali-rare earth fluorides (BaGdF 5 , NaYF 4 ), etc. 10 On the other hand, it has also been reported that the presence of Al 2 O 3 in LiTaO 3 -SiO 2 glass system aids the crystallization process to obtain transparent glass-ceramics due to higher nucleation rate in terms of promoting phase separation in the glass-network. 4 In particular, when we look into the literature on various aluminosilicate-based oxyfluoride glass systems, a wide range of variation in Al 2 which yield transparent glass-ceramics containing fluoride nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…9 Thus, inclusion of alumina in a silicate matrix may provide advantages like increased chemical durability, viscosity, hardness, thermal stability, and comparable thermal expansion properties. 10 On the other hand, it has also been reported that the presence of Al 2 O 3 in LiTaO 3 -SiO 2 glass system aids the crystallization process to obtain transparent glass-ceramics due to higher nucleation rate in terms of promoting phase separation in the glass-network. 11 Similarly, in Li 2 O-SiO 2 system, it has been observed that Al 2 O 3 simultaneously suppress the immiscibility temperature and promotes both crystallization process and liquidliquid phase separation.…”
Section: Introductionmentioning
confidence: 99%